A Study of Pre-service and In-Service Teachers’ Understanding of Electrochemical Cells - VIDYAPATI, T.J.; PAREEK, RAM BABU; RAO, T.V.S. PRAKASA (SCHOOL SCIENCE, 2006)
A survey of recent literature reveals that a good number o f research reports/articles appeared in national and international journals on students’ understanding of various science concepts. The researchers have evolved different terms to describe these understandings. Driver and Easley (1978) preferred to call them pre-conceptions; Gilbert, Osborne and Fensham (1982) used the term children’s science; Cho, Kahle and Nordland (1985) evolved the term misconceptions; Driver and Erickson (1983) used the term alternative frameworks and Fischer and Lipson (1986) preferred to address the same as students’ errors.